Abbreviated review for psychologists of the second most common cause of neurodegenerative disease in elderly people - Rosangela Bertelli; José João Pinhanços de Bianchi; Eduardo Chaves Cruz (Desafio Singular, 2009)
Malignant forms of cognitive decline are caused by a variety of neuropathological conditions. Dementia with Lewy bodies (DLB) is among such conditions. Even though such a condition represents the second most frequent cause of neurodegenerative dementia in elderly people, it is still very little known by psychologists. Psychologists can play a very important role in the process of cognitive evaluation and differential diagnosis between this neurodegenerative condition and neuropsychiatric conditions. Knowledge of DLB is thus extremely important and it may mean a decrease in fatality rate.